2016
DOI: 10.1007/978-3-319-28910-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Personalized QoS Prediction of Cloud Services via Learning Neighborhood-Based Model

Abstract: The explosion of cloud services on the Internet brings new challenges in service discovery and selection. Particularly, the demand for efficient quality-ofservice (QoS) evaluation is becoming urgently strong. To address this issue, this paper proposes neighborhoodbased approach for QoS prediction of cloud services by taking advantages of collaborative intelligence. Different from heuristic collaborative filtering and matrix factorization, we define a formal neighborhood-based prediction framework which allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Wu et al [36] put forward a learning neighbourhood-based prediction method. In this approach, the previous profile record is critical for the prediction of a service violation.…”
Section: Releated Studiesmentioning
confidence: 99%
“…Wu et al [36] put forward a learning neighbourhood-based prediction method. In this approach, the previous profile record is critical for the prediction of a service violation.…”
Section: Releated Studiesmentioning
confidence: 99%
“…The effectiveness of the approach is validated using a probabilistic checking model, PRISM, and a Smart Grid case study. Wu et al [18] proposed a learning neighborhood-based prediction method to predict personalized QoS parameters. In their proposed model, machine-learning methods are used to build a neighborhood-based approach which gives optimal results compared to other collaborative filtering methods, such as a memory-based method.…”
Section: Qos Prediction In Cloud Service Managementmentioning
confidence: 99%
“…They concluded that ML based methods out-performed the TS based methods in predicting the service quality. A neighborhood-based approach is suggested in [15] for quality of service estimation. Comparetively, their proposed method produce optimal results.…”
Section: Introductionmentioning
confidence: 99%